Alternative method for determining anaerobic threshold in rowers - Giovani dos Santos Cunha; Rafael Reimann Baptista; Jerri Luiz Ribeiro; Alvaro Reischak de Oliveira (Universidade Federal de Santa Catarina, 2008)
In rowing, the standard breathing that athletes are trained to use makes it difficult, or even impossible, to detectventilatory limits, due to the coupling of the breath with the technical movement. For this reason, some authors have proposeddetermining the anaerobic threshold from the respiratory exchange ratio (RER), but there is not yet consensus on what valueof RER should be used. The objective of this study was to test what value of RER corresponds to the anaerobic thresholdand whether this value can be used as an independent parameter for determining the anaerobic threshold of rowers. Thesample comprised 23 male rowers. They were submitted to a maximal cardiorespiratory test on a rowing ergometer withconcurrent ergospirometry in order to determine VO2máx and the physiological variables corresponding to their anaerobicthreshold. The anaerobic threshold was determined using the Dmax (maximal distance) method. The physiological variableswere classified into maximum values and anaerobic threshold values. The maximal state of these rowers reached VO2(58.2±4.4 ml.kg-1.min-1), lactate (8.2±2.1 mmol.L-1), power (384±54.3 W) and RER (1.26±0.1). At the anaerobic thresholdthey reached VO2 (46.9±7.5 ml.kg-1.min-1), lactate (4.6±1.3 mmol.L-1), power (300± 37.8 W) and RER (0.99±0.1). Conclusions- the RER can be used as an independent method for determining the anaerobic threshold of rowers, adopting a value of0.99, however, RER should exhibit a non-linear increase above this figure.